Covid collection (Firenze University Press, 2021)
The speed at which the COVID-19 pandemic spread across the world and the need to rapidly disseminate research outcomes highlighted the crisis of the traditional publication process, drawing attention to the scarce responsiveness to the rapid advances in research and technology, and to the global problem of closed access articles. The pandemic response created an urgency, and this urgency immediately prompted virtuous trends in academic publishing: new tools for researchers and readers, easily accessible data, a reduction in publication times (still ensuring high quality standards) and, above all, a move toward more open-access publishing. Firenze University Press has been one of the first promoter of this unprecedent "new deal" in academic publishing, and actively contributed to its realization with a rapid, open, and transparent approach. Starting from March 28, 2020 the Journals published by Firenze University Press launched a series of special calls for papers concerning the multiple and multifaceted issues related to Covid-19 in a wide range of fields, including biology, chemistry, education, sociology, economics, history, and so forth.